Non-Pharmacological Management of Sleep Disorders in the Older Adults: The Role of Aromatic Footbath-Hydrotherapy - Rizqi Wahyu Hidayati; Anastasia Suci Sukmawati; Yuli Astuti (Journal Of Nursing Practice, 2026)
Background: The increase in physiological symptoms in the elderly has an impact on reducing the quality of sleep. This decrease in sleep quality has an impact on health both physically and psychologically. One of the psychological impacts is depression. Various studies explain that depression can lead to distortion of thoughts, decreased memory, increased risk of suicide, and death. Purpose: The aimed to determine the effectiveness of the complementary therapy, especially aromatic footbath-hydrotherapy in reducing sleep disorders among the elder adults. The potential harming of the study were allergic and foot-wound, however the researcher select the participants based on inclusions and exclusions criteria. Methods: The method used was quasi experiment with pre-post control group. The group was divided into three with the number of respondents, there was 39 elderly consumptions of Sahdu tea, 38 elderly consumptions of "wedhang uwuh", and 30 elderly aromatic footbath hydrotherapy. The inclusions were elderly (>= 55 years old), independent activities, good verbal communication. The exclusions were allergic with the herbal’s composition, severe dementia, and severe cardiovascular disease. The data was located in Candibinangun, Ambarketawang, and Balecatur D.I. Yogyakarta in 2024. The data were scattered abnormally so using non- parametric tests to see the effectiveness of therapy. The questionnaire used PSQI. The one-way ANOVA test was implemented in the study. Results: Based on Wilcoxon test, Sahdu tea had effectively in latency and the total PSQI score; Wedhang Uwuh Javanese Drink had only effectively in sleep disorders, and the latest therapy, aromatic footbath hydrotherapy had effectively in quality, latency, duration, sleep disorder, dysfunctional, and total score of PSQI. One way ANOVA found that aromatic footbath hydrotherapy was most effective in reducing elderly sleep disorders (p: 0.000). Conclusion: Aromatic footbath hydrotherapy (AH) was most effective in reducing elderly sleep disorders. However, the weakness of this study is that researchers cannot control the stability of water temperature during therapy.